Changes in NR2ab Antibody Levels in the Blood of Patients Depending on their Condition: Acute or Chronic Cerebral Ischaemia - Akhmetzhanova, Zauresh; Jaxybayeva, Altynshash; Imanova, Aliya; Kamkhen, Vitaliy; Akshulakov, Serik (Acta medica Lituanica, 2026)
Aim: The study aimed to determine the efficacy of antibodies to the NR2ab subunits of the N-methyl-D-aspartate (NMDA) receptor (NR2ab) as a biomarker for the differential diagnosis of acute and chronic cerebral ischaemia (CCI) among patients in Kazakhstan. Materials and methods: The study involved 52 patients with CCI classified as second-degree according to the Fazekas scale and 47 patients with acute ischaemic stroke (AIS), rated at 16–20 on the National Institutes of Health Stroke Scale (NIHSS), who were hospitalised in stroke centres within 24 hours of the first symptoms of stroke and confirmed by magnetic resonance imaging. Serum samples were collected to determine NR2ab antibody levels. Results: The results of the study showed that the mean level of NR2ab in patients with CCI was 1.42 ng/ml (95% CI: 1.2–1.6), while in patients with AIS it was 1.99 ng/ml (95% CI: 1.7–2.3). Statistical analysis revealed a significant difference between the groups (p=0.003), and logistic regression determined the prognostic significance of NR2ab with a coefficient of 1.885. The Receiver Operating Characteristic (ROC) curve analysis showed a diagnostic accuracy of 0.675, which indicates the prospects of using this biomarker to detect acute cerebral ischaemia. Conclusions: The results confirm that determining the level of NR2ab can be a useful tool for a timely diagnosis and selection of adequate treatment, especially in conditions of limited access to neuroimaging. Incorporation of this method into the standard diagnostic process can improve the efficiency of detecting ischaemic disorders and optimise patient care.